THE USE OF HALF A CROSSWORD PUZZLE IN TEACHING VOCABULARY TO ELEMENTARY SCHOOL STUDENTS - Ahmad Syarif; Fitrawati Fitrawati (Journal of English Language Teaching, 2016)
This paper explains about how to implement half a crossword puzzle in teaching vocabulary related to job and people for Elementary School students grade two. This game could be played in two groups, which are group A and B. In this game, teacher distributes different board for each group. Half of each board already filled and the filling boards are the answers of the opposite group. To play this game, group A gives a clue about a word to group B, and then group B tries to guess the clue given by group A. The group that can fill all the blank part correctly will be the winner. This game eases the students in mastering vocabularies related to job and people in English. It could also increase the students’ motivation because this game is interesting and fun.